2012
DOI: 10.1007/s10545-012-9550-6
|View full text |Cite
|
Sign up to set email alerts
|

Demographics, diagnosis and treatment of 256 patients with tetrahydrobiopterin deficiency in mainland China: results of a retrospective, multicentre study

Abstract: This study provides valuable information on the current and historical situation of BH4 deficiency in mainland China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 18 publications
5
29
0
Order By: Relevance
“…A series of national and local administrative measures were implemented in 2009 to diminish the geographic differences in the coverage of newborn screening (The technical specification of newborn screening; Mei et al 2013a, b). With the expansion of its coverage, the number of neonates screened increased from 5 million in 2006 to more than 10 million in 2013 (Cao et al 2009; Wang et al 2010; Ye et al 2013). According to the report of “The technical specification of newborn screening”, the proportion of screening was 87.98 %(total number of newborn was 16,714,051, the total number of screened was 14,705,320) in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…A series of national and local administrative measures were implemented in 2009 to diminish the geographic differences in the coverage of newborn screening (The technical specification of newborn screening; Mei et al 2013a, b). With the expansion of its coverage, the number of neonates screened increased from 5 million in 2006 to more than 10 million in 2013 (Cao et al 2009; Wang et al 2010; Ye et al 2013). According to the report of “The technical specification of newborn screening”, the proportion of screening was 87.98 %(total number of newborn was 16,714,051, the total number of screened was 14,705,320) in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In general, BH 4 is used in combination with l ‐dopa and 5‐HTP, because it is ineffective in correcting neurotransmitter deficiencies due to poor permeability through the blood‐brain barrier . During treatment, the recommendation is to adjust the BH 4 dose to maintain the serum phenylalanine level below 120 μmol/L …”
Section: Resultsmentioning
confidence: 99%
“…A recent study in Mainland China estimated that only 37.3% of patients had an intelligence quotient below 85, but did not indicate the proportion requiring long-term residential care, and their figures included diseases other than PTPS deficiency and those already picked up by an expanded NBS programme. 52 Other studies have reported that delayed diagnosis and treatment could result in severe disability in 80% of patients in whom PTPS deficiency is the main genetic defect. 21,22 It is usually recommended that indirect costs (for which there is no payment made but for which a cost nonetheless exists) should be included in economic evaluation studies for health policies.…”
Section: Discussionmentioning
confidence: 99%